Low noise DC amplifier with selectable gain and auto-zero functionality for use with modern integrated A/D converters - Tomíček, Pavel; Levek, Vladimír (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2022)
This paper presents the design and noise measurements of amplifier suitable for use with modern integrated A/D converters. Proposed topology is capable of both amplifying and attenuating its input signal to utilize whole input voltage range of A/D converters. Experimental version achieved full scale input voltage range from ±15 V to ±15 mV. Suppression of offset error associated with amplifier and A/D converter systems is realized using auto-zero scheme. Resulting amplifier used in conjunction with digital filters can achieve more than 20 noise free bits on all gain settings.
Keywords: low noise, DC amplifier, selectable gain, auto-calibration, A/D converter